THE MAIN PROVISIONS OF SCIENTIFIC AND PRODUCTION ASSOCIATION’s product POLICY FORMATION - I. Razumov (Вестник университета, 2019)
Main provisions of formation of scientific and production associations product policy are assumed. The content of the category "product policy" is clarified, This category should be considered from the point of view of the design approach, and from the point of view of process approach. The necessity of use of this item as a base to reduce the uncertainty inherent in tasks of similar complexity, the model of the problem situation is shown. The expediency of presenting such models in the form of Ishikawa diagrams is established.